Transforming Physical Hands-on Laboratory Practice to Remote Laboratory Experimentation : A COVID-19 Experience - Norazlina, Bateni; Rosmina, Ahmad Bustami; Al Sidqi, Hassan; Dyangku Salma, Awang Ismail; Md Abdul, Mannan; Mohammad Sapian, Mohamed Kasim; Mohd Zaidi, Serah (UNIMAS Publisher, 2023)
KNS 2601 is a laboratory course for Hydraulics and Geotechnical taught to Second-year students. The course exposes students to the technical background of hydraulics and geotechnical standard tests. Students are expected to comprehend and apply the principles of analysis and the scope of works in the hydraulics and geotechnical field. It is aimed to enhance students understanding from hands-on experience through standardized procedure and equipment provided in the laboratory. The experiments conducted are open-ended laboratory experimentations, where students need to come out with their own procedure and hypothesis. The course covers the psychomotor domain of P4 (Mechanism) and Critical Thinking (CT) skills. However, due to the COVID-19 pandemic, the instructors needed to outline a practical solution that could satisfy the outlined learning outcomes and expected taxonomies as quickly as possible. The pandemic hit us during the mid-semester break, when most students have completed half of the laboratory experiments (total of eight laboratory sessions) – leaving the course half-finished. Hence, a digitalbased learning experience with an introduction to virtual laboratory practice was introduced. Demonstration videos were prepared for students to access and ‘experience’ the experiments whilst not being physically present in the laboratory.